2021
DOI: 10.1111/aec.13061
|View full text |Cite
|
Sign up to set email alerts
|

The use of taxonomic relationships among species in applied ecological research: Baseline, steps forward and future challenges

Abstract: Taxonomy is more than a mere exercise of nomenclature and classification of biological diversity: it profiles the identity of species by investigating their biological and ecological traits. Taxonomy is intimately related to ecology which, in turn, cannot be a mere exercise in describing ecological patterns, but instead requires deep knowledge of species' biological structures, roles, interactions and functions. Thus, the study of taxonomic and phylogenetic relatedness of species is of paramount importance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 146 publications
1
11
0
Order By: Relevance
“…In terms of depth gradients, the increase of species richness (S) in the 200-400 m depth range agrees with previous local studies (Lange, 2012) that observed highest richness at depths of 300-399 m. Our results, however, contrast with the Duffy et al (2014) submarine canyon observations of species richness steadily increasing with depth between 200-700 m. This may be an artifact of the low number of samples (n < 11) represented in the 501-700 m range, as species richness is dependent on sampling effort (Clarke and Warwick, 1998;1999;Bevilacqua et al, 2021). The average taxonomic distinctiveness index (delta +), on the other hand, showed a fluctuation and opposing trend, whereby the lowest measure was identified at 201-300 m (the second most speciose depth) and the highest at 601-1000 m (least species richness).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of depth gradients, the increase of species richness (S) in the 200-400 m depth range agrees with previous local studies (Lange, 2012) that observed highest richness at depths of 300-399 m. Our results, however, contrast with the Duffy et al (2014) submarine canyon observations of species richness steadily increasing with depth between 200-700 m. This may be an artifact of the low number of samples (n < 11) represented in the 501-700 m range, as species richness is dependent on sampling effort (Clarke and Warwick, 1998;1999;Bevilacqua et al, 2021). The average taxonomic distinctiveness index (delta +), on the other hand, showed a fluctuation and opposing trend, whereby the lowest measure was identified at 201-300 m (the second most speciose depth) and the highest at 601-1000 m (least species richness).…”
Section: Discussionsupporting
confidence: 87%
“…Canyon areas were defined by higher species richness and diversity as compared to non-canyon areas. Even though sampling biases occurred, the use of gamma+ as the basis of testing multivariate responses to predictor variables accounted for this by considering taxonomic relationships of species at all levels (Clarke et al, 2006;Bevilacqua et al, 2021). Nonetheless, high species variability at both the canyon and non-canyon stations was documented in which taxonomic groups discriminating the comparison were present.…”
Section: Discussionmentioning
confidence: 99%
“…Note that, whereas taxonomic distinctness uses a taxonomic tree to calculate distances among species, it is possible also to perform the calculations using a functional (or other) distance matrix among species instead (see Bevilacqua et al . 2021, this volume ). We performed the TAXDTEST algorithm separately for each depth stratum, using a normalised Euclidean distance matrix based on the 8 functional traits averaged across the dataset at the species level ( n = 144).…”
Section: Methodsmentioning
confidence: 94%
“…Stanislau Bevilacqua and colleagues then provide a timely overview of approaches that integrate taxonomic information in multivariate ecological studies; by pointing to present and future methods, this contribution is both retrospective and forward‐looking in its scope (Bevilacqua et al . 2021). The next two contributions – one led by Odette Howarth and the other led by Lizzy Myers – deal with precisely the sort of extensions envisaged by the Bevilacqua et al .…”
Section: A Special Issuementioning
confidence: 99%